Difference in volatile composition between the pericarp tissue and inner tissue of tomato (Solanum lycopersicum) fruit. Issue 1 (4th July 2017) - Wang, Libin; Qian, Chunlu; Bai, Jinhe; Luo, Weiqi; Jin, Changhai; Yu, Zhifang
Abstract: Numerous studies have reported the volatile profiles in the whole fruit or pericarp tissue of tomato ( Solanum lycopersicum ) fruit; however, information is limited on the volatile composition in the inner tissue and its contribution to tomato aroma. For this, the pericarps and inner tissues of "Moneymaker, " "UglyRipe, " and "FL 47" fruits were separated before volatile analysis. Result showed that the volatile profiles were quite similar between the pericarp and inner tissue, suggesting the inner tissues also have a contribution to overall aroma quality. Besides the difference in volatile profile among cultivars, a higher concentration of alcohols was observed in the inner tissues of tomato fruit in comparison with that in the pericarp, which was associated with higher levels of 3‐methylbutanal, 2‐methylbutanal, 3‐methylbutanol, and 2‐methylbutanol in the inner tissue. These results also imply that different sampling methods might impact tomato aroma quality, which needs further verification via sensory penal. Practical applications: The information on the volatile profile in the inner tissue and its contribution to tomato aroma is still rudimentary. In this study, the pericarp and inner tissue were separated from three tomato cultivars of different genetic background, and the volatile compositions were analyzed with HS‐SPME‐GC‐MS. Result showed that the volatile compositions were quite similar between the pericarp and inner tissue, suggesting that the inner tissues also have a contribution to overall aroma quality. Besides, a higher concentration of alcohols was observed in the inner tissues of tomato fruit in comparison with that in the pericarp, which was associated with higher levels of 3‐methylbutanal, 2‐methylbutanal, 3‐methylbutanol, and 2‐methylbutanol in the inner tissue. This study will provide the researchers and consumers some useful information on volatile composition in the inner tissue, its contribution to tomato aroma, and the impact of different sampling methods on the volatile profile.